A visible-light-driven core-shell like Ag2S@Ag2CO3 composite photocatalyst with high performance in pollutants degradation. (August 2016) - Yu, Changlin; Wei, Longfu; Zhou, Wanqin; Dionysiou, Dionysios D.; Zhu, Lihua; Shu, Qing; Liu, Hong
Abstract: A series of Ag2 S-Ag2 CO3 (4%, 8%, 16%, 32% and 40% Ag2 S), Ag2 CO3 @Ag2 S (32%Ag2 S) and Ag2 S@Ag2 CO3 (32%Ag2 S) composite photocatalysts were fabricated by coprecipitation or successive precipitation reaction. The obtained catalysts were analyzed by N2 physical adsorption, powder X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, Raman spectroscopy, UV–vis diffuse reflectance spectroscopy and photocurrent test. Under visible light irradiation, the influences of Ag2 S content and core-shell property on photocatalytic activity and stability were evaluated in studies focused on the degradation of methyl orange (MO) dye, phenol, and bisphenol A. Results showed that excellent photocatalytic performance was obtained over Ag2 S/Ag2 CO3 composite photocatalysts with respect to Ag2 S and Ag2 CO3 . With optimal content of Ag2 S (32 wt%), the Ag2 S-Ag2 CO3 showed the highest photocatalytic degradation efficiency. Moreover, the structured property of Ag2 S/Ag2 CO3 greatly influenced the activity. Compared with Ag2 S-Ag2 CO3 and Ag2 CO3 @Ag2 S, core-shell like Ag2 S@Ag2 CO3 demonstrated the highest activity and stability. The main reason for the boosting of photocatalytic performance was due to the formation of Ag2 S/Ag2 CO3 well contacted interface and unique electron structures. Ag2 S/Ag2 CO3 interface could significantly increase the separation efficiency of the photo-generated electrons (e − ) and holes (h + ), and production of OH radicals. More importantly, the low solubility of Ag2 S shell could effectively protect the core of Ag2 CO3, which further guarantees the stability of Ag2 CO3 . Graphical abstract: Highlights: High visible-light-driven photocatalytic performance in pollutants degradation. Ag2 S content and core-shell property distinct influence activity and stability. Unique Ag2 S/Ag2 CO3 interface largely boosts e − /h + pairs separation and OH radicals production. Ag2 S shell prevents the dissolution of Ag2 CO3 core.